PENGARUH TUNNELING INCENTIVE, MEKANISME BONUS, BEBAN PAJAK DAN LAVERAGE TERHADAP KEPUTUSAN PERUSAHAAN MELAKUKAN TRANSFER PRICING - Hafira Isnain; Dirvi Surya Abbas; Hamdani, Hamdani; Budi Rohmansyah (Akuntansi, 2022)
The development of the business world is currently a trigger for the growth of multinational companies whose operational scope is not only centered on one country, but in several countries. One of the problems faced by multinational companies is the difference in tax rates between countries. The development of the business world is currently a trigger for the growth of multinational companies whose operational scope is not only centered on one country, but in several countries. One of the problems faced by multinational companies is the difference in tax rates between countries. The population of this study includes all manufacturing companies of the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling technique uses the Purposive Sampling technique. Based on the criteria that have been established and obtained by 8 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results showed that tunneling incentives have no effect, bonus mechanisms have a positive effect, tax burdens do not affect the company's decision to transfer pricing and tunneling incentives,Bonus mechanisms and tax burdens simultaneously have a significant effect on the company's decision to make transfer pricing. Meanwhile, the partial bonus mechanism has a significant effect on the company's decision to transfer pricing.